2014
DOI: 10.1111/sltb.12065
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk Assessment and Risk Formulation Part I: A Focus on Suicide Ideation in Assessing Suicide Risk

Abstract: The main procedure used by clinicians to determine whether an individual may be at risk of suicidal behaviors is the suicide risk assessment (SRA). The purpose of the SRA is to identify risk and protective factors that then provide the data for the formulation of suicide risk. The suicide risk formulation (SRF) assigns a level of suicide risk that ideally leads to triage and treatment deemed appropriate for that level of risk. Some of the problems with the SRA are explored here, with an emphasis on addressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 64 publications
2
70
0
1
Order By: Relevance
“…However, it is common practice for many clinicians to ask only about the presence of suicide ideation (Silverman & Berman, ). LSSN, and the LRAMP within it, were designed to guide clinicians through conducting a thorough suicide risk assessment that covers the evidence‐based factors in each of the recommended domains.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is common practice for many clinicians to ask only about the presence of suicide ideation (Silverman & Berman, ). LSSN, and the LRAMP within it, were designed to guide clinicians through conducting a thorough suicide risk assessment that covers the evidence‐based factors in each of the recommended domains.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, we have articulated that traditional guidelines for conducting an SRA have overemphasized long-standing approaches that have little empirical support [53]. Among these unquestioned approaches is that the presence of communicated suicidal ideation has traditionally been the gateway to the investigation of whether an individual might be "suicidal."…”
Section: Suicide Risk Assessmentmentioning
confidence: 98%
“…These authors concluded that no one factor, or combination of factors, was strongly associated with suicide in the year after discharge and, further, that risk categorization is of no value in efforts to decrease the numbers of patients who will die by suicide after hospital discharge. Our interpretation of this meta-analysis is that the "low risk" patients may have been misdiagnosed or poorly assessed, in part because once they denied suicidal ideation they were deemed to be free of suicide risk and ready for discharge [53].…”
Section: Just How Reliable Are Clinicians' Judgments Of Levels Of Risk?mentioning
confidence: 98%
See 1 more Smart Citation
“…Silverman and Berman [14] suggest that assessing suicidal risk in clinical practice is influenced by the skills and philosophy of the individual clinician. Nonetheless, there are various guidelines on what to assess including life history, previous suicidal attempts and mental state [15–17], `along with helpful frameworks for how to assess risk [12, 18, 19].…”
Section: Introductionmentioning
confidence: 99%